1989
DOI: 10.3109/02699058909004563
|View full text |Cite
|
Sign up to set email alerts
|

Employment outcomes of persons following traumatic brain injury: pre-injury, post-injury, and supported employment

Abstract: This paper provides a prospective analysis of the pre-injury, post-injury and supported employment work histories of 20 persons who survived a severe head injury. All persons had a very limited or inconsistent work history post-injury, due to the severity of the injury. Data are presented on the placement outcomes and include factors such as wages, hours worked, months of employment and type of occupation. The supported employment model is described and the job coach approach is presented in some detail. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…In the late eighties, practical strategies to help individuals with TBI with return to work were just evolving and implementation of supported employment for individuals with TBI has been described in detail. 36,37 This model was based on demonstration projects with other populations and had become a vocational rehabilitation option by way of the 1986 Amendments to the Rehabilitation Act. 38 Today, supported employment is defined as "competitive work in integrated work settings, or employment in integrated work settings in which individuals are working toward competitive work, consistent with the strengths, resources, priorities, concerns, abilities, capabilities, interests, and informed choice of the individuals."…”
Section: Nonapplicablementioning
confidence: 99%
“…In the late eighties, practical strategies to help individuals with TBI with return to work were just evolving and implementation of supported employment for individuals with TBI has been described in detail. 36,37 This model was based on demonstration projects with other populations and had become a vocational rehabilitation option by way of the 1986 Amendments to the Rehabilitation Act. 38 Today, supported employment is defined as "competitive work in integrated work settings, or employment in integrated work settings in which individuals are working toward competitive work, consistent with the strengths, resources, priorities, concerns, abilities, capabilities, interests, and informed choice of the individuals."…”
Section: Nonapplicablementioning
confidence: 99%
“…Several factors have been identified that add predictive value. These include injury severity, age at time of injury, number of neuropsychological deficits, level of physical disability, premorbid employment, and educational level [3,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Kreutzer et al [3] and Wehman et al [4,7] discuss a means to tailor individual compensatory strategies to overcome the isolated effects of laboratory-type training. This is a good start and shows promise in case studies, but more should be done.…”
Section: Discussionmentioning
confidence: 99%